Airfoil optimization to improve power performance of a high-solidity vertical axis wind turbine at a moderate tip speed ratio. (1st May 2018) - Ma, Ning; Lei, Hang; Han, Zhaolong; Zhou, Dai; Bao, Yan; Zhang, Kai; Zhou, Lei; Chen, Caiyong
Abstract: The relatively low power coefficient restricts the wide application of vertical axis wind turbines (VAWTs). An effective solution to this problem is to design specific airfoil profiles which directly influence the capture ratio of wind power. The main aim of the present study is to develop an automatic airfoil profile optimization system to improve the power performance of a VAWT. A three-bladed high-solidity VAWT is adopted as the research object with its chord length, blade span and rotor diameter being 0.2 m, 0.8 m and 0.8 m, respectively. The optimization is conducted at a moderate tip speed ratio (TSR) with a value of 1.0 and the method of coupled CFD simulations with genetic algorithms is employed. The following points make this paper different from previous studies: (a) introducing Multi-Island Genetic Algorithm to optimize airfoils for VAWTs; (b) investigating the airfoil as part of the VAWT rather than as a single isolated body with 3D simulations. The results show that the power coefficient of the VAWT equipped with the optimized blades sensibly improves at all TSRs from 0.4 to 1.5 and the maximum growth rate of it occurs at TSR = 0.9 with a value of 26.82%. The integrated optimization system used in this paper provides an effective way to generate suitable airfoil profiles for given VAWTs with the goal to achieve higher power efficiency. Highlights: An automatic airfoil profile optimization system for VAWTs is established. 3D CFD simulation and Multi-Island Genetic Algorithm are used in the optimization. The optimized airfoil profile becomes non-symmetric with the thickness enlarged. The power performance of the VAWT with the optimized airfoil sensibly improves.